Preference of surgical procedure for the forefoot deformity in the rheumatoid arthritis patients—A prospective, randomized, internal controlled study. Issue 3 (May 2015) - Tada, Masahiro; Koike, Tatsuya; Okano, Tadashi; Sugioka, Yuko; Wakitani, Shigeyuki; Mamoto, Kenji; Inui, Kentaro; Nakamura, Hiroaki
Abstract Objectives. The deformed rheumatoid forefoot may be treated with resection of lesser metatarsal heads combined with arthrodesis or resection of the first metatarsophalangeal joint. Recurrent hallux valgus deformity has been reported by resection. We performed a prospective, randomized, internal-controlled study to compare results between arthrodesis and resection. Methods. We resected the lesser metatarsal heads bilaterally and performed arthrodesis of the first metatarsophalangeal joint on one side and resection on the opposite side. We investigated 26 patients (52 feet) who were followed at least one year. Patients were assessed for clinical score, hallux valgus angle (HVA), angle between first and second metatarsals, and angle between first and fifth metatarsals preoperatively, postoperatively and at final follow-up. We evaluated callosities, claw toes, recurrences, and procedure preferences. Results. The mean follow-up period was 4.1 years. No significant differences between arthrodesis and resection were seen, with the exception of HVA. That was significantly less on arthrodesis side (11.5°) than on resection side (17.0°, p < 0.05). Seven callosities on resection side and four on arthrodesis side were observed. On resection side, hallux valgus deformity often recurred (15.3%). Patients expressed a significant preference for arthrodesis over resection (p = 0.008). Conclusions. Arthrodesis provides better results for maintaining HVA.